THE BIRTH OF RED IDEALS: COMMUNISM TOOK ROOT IN INDIA - Bibimol. R.B; Seena, Anand Lali; K.K.Thanammal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The formation of the Communist Party of India (CPI) in 1925 marked a pivotal moment in Indian politics, as it sought to align with the global Communist Movement while addressing local issues of class struggle. Key figures like M.N.Roy were instrumental in introducing Marxist ideology which resonated with a segment of the Indian society grappling with exploitation, suppression and oppression. The CPI's early activities focused on labour and peasant movements, aiming to mobilise the working class against colonial rule. These efforts were often met with repression, as the British authorities viewed the communists as a significant threat to their imperialistic reign. In post-independent India, the Communist Movement experienced both progression and fragmentation. Initially supportive of the Indian National Congress under Jawaharlal Nehru, the CPI was on the verge of facing ideological rifts, leading to a split in 1964 that gave birth to the Communist Party of India (Marxist) (CPI-M). The CPI-M (CPI (M)) gained notable success in State politics, particularly in Kerala and West Bengal, where it implemented significant land reforms and social welfare policies. Despite the many challenges encountered, the Left Movement continues to advocate for workers' rights and social justice, emphasising its enduring relevance in contemporary Indian politics.